Creation of a national emergency medicine enhanced competency directory for residency training. Issue 4 (4th March 2018) - Argintaru, Niran; Baylis, Jared; Pritchard, Jodie; Mulla, Ali; Gray, Alice; Hart, Alexander; Bova, Christina; Armstrong, Teri-Leigh; Taher, Ahmed
Abstract: Canadian emergency medicine Royal College residency training allows for pursuing extra training in enhanced competency areas. A wealth of enhanced competency training opportunities exist nationally. However, the search for the right fit is a challenging one because there is no centralized resource that catalogues all of these opportunities. A working group of the Canadian Association of Emergency Physicians (CAEP) Resident Section was assembled in 2016 to create a freely accessible and comprehensive directory of Canadian enhanced competency areas. The working group used stakeholder surveys (of residents, recent graduates, and faculty members), social media engagement, and program website searches. Information was collated into the first edition of a national enhanced competency directory, which is available at no cost athttp://caep.ca/sites/caep.ca/files/enhancedcompdoc.pdf . Limitations include the scope defined by the working group and survey responses. A biannual update is also incorporated into the CAEP Resident Section portfolio to ensure it remains up-to-date. RÉSUMÉ: La formation en médecine d'urgence du Collège royal des médecins et chirurgiens du Canada au niveau de la résidence prévoit la poursuite d'une formation supplémentaire dans des domaines de compétence fine. Il existe, à l'échelle nationale, un large éventail de possibilités de formation dans ces domaines. Toutefois, la recherche du champ d'intérêt le plus approprié est particulièrement difficile, car il n'existe pas de répertoire centralisé de toutes les spécialités possibles. Un groupe de travail de la section des résidents de l'Association canadienne des médecins d'urgence (ACMU) a donc été formé en 2016 afin de constituer un répertoire gratuit et complet de ces domaines de compétence fine, existant au Canada. Pour ce faire, le groupe de travail a mené des enquêtes parmi divers intervenants (résidents, diplômés récents, enseignants), fait appel aux médias sociaux et effectué des recherches dans des sites Web de programmes. Les renseignements recueillis ont été réunis dans la première édition du répertoire national de compétences fines, accessible gratuitement àhttp://caep.ca/sites/caep.ca/files/enhancedcompdoc.pdf . Le répertoire comporte toutefois des faiblesses, notamment la portée de l'inventaire déterminée par le groupe de travail et les réponses au questionnaire d'enquête. Enfin, une mise à jour semestrielle est prévue dans le programme d'activités de la section des résidents de l'ACMU afin s'assurer qu'il reste à jour.